PENGEMBANGAN BAHAN AJAR COSMIC (COMIC OF SULTANATE’S MAJOR INDEPENDENCE CONFLICT) PADA MATERI PERANG PALEMBANG TAHUN 1819-1821 Di KELAS XI MAN 1 OGAN ILIR - Yoga Febrian Syahputra; Muhammad Reza Pahlevi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The limited innovation of learning media in studying local history with increasingly advanced technological developments has not been fully conveyed, materials such as the Palembang War of 1819-1821 are still little studied so that innovative teaching materials are needed that are in accordance with technological developments and the needs of students. This study aims to develop Cosmic media in Heyzine-based history learning that is valid, interesting and practical. This study uses the Alessi & Trollip development model which was implemented in class XI F1 MAN 1 Ogan Ilir. The validation results of this study show a value from media experts of 4.57, and a value from material experts of 4.69, both of which are included in the very valid category. The level of practicality of Cosmic can be seen from the value of educator responses which show a value of 97.3% and the value of student responses reaching 89.94% which when recapitulated can reach a value of 90.22% with a very good category. Thus, it can be concluded that the Heyzine-based Cosmic product with the material of the Palembang War of 1819-1821 is suitable for use as a learning medium, especially for learning history.